Identifying social cognition subgroups in euthymic patients with bipolar disorder: a cluster analytical approach. Issue 1 (17th January 2022) - Varo, C.; Solé, B.; Jiménez, E.; Bonnín, C. M.; Torrent, C.; Valls, E.; Lahera, G.; Martínez-Arán, A.; Carvalho, A. F.; Miskowiak, K. W.; Vieta, E.; Reinares, M.
Abstract: Background: Bipolar disorder (BD) is associated with social cognition (SC) impairments even during remission periods although a large heterogeneity has been described. Our aim was to explore the existence of different profiles on SC in euthymic patients with BD, and further explore the potential impact of distinct variables on SC. Methods: Hierarchical cluster analysis was conducted using three SC domains [Theory of Mind (ToM), Emotional Intelligence (EI) and Attributional Bias (AB)]. The sample comprised of 131 individuals, 71 patients with BD and 60 healthy control subjects who were compared in terms of SC performance, demographic, clinical, and neurocognitive variables. A logistic regression model was used to estimate the effect of SC-associated risk factors. Results: A two-cluster solution was identified with an adjusted-performance group ( N = 48, 67.6%) and a low-performance group ( N = 23, 32.4%) with mild deficits in ToM and AB domains and with moderate difficulties in EI. Patients with low SC performance were mostly males, showed lower estimated IQ, higher subthreshold depressive symptoms, longer illness duration, and poorer visual memory and attention. Low estimated IQ (OR 0.920, 95% CI 0.863–0.981), male gender (OR 5.661, 95% CI 1.473–21.762), and longer illness duration (OR 1.085, 95% CI 1.006–1.171) contributed the most to the patients clustering. The model explained up to 35% of the variance in SC performance. Conclusions: Our results confirmed the existence of two discrete profiles of SC among BD. Nearly two-thirds of patients exhibited adjusted social cognitive abilities. Longer illness duration, male gender, and lower estimated IQ were associated with low SC performance.